Seroprevalence of HBV and HCV among HIV-infected adults in China according to route of HIV infection: high rate of HBV and HCV exposure. (October 2012) - Zhang, Fujie; Zhou, Shuntai; Chen, Xi; Ji, Guoping; Lu, Ying; Wu, Yasong; Liu, Zhongfu; Shang, Hong
Coinfection of viral hepatitis, specifically HBV and HCV, has been increasingly observed among patients infected with HIV. However, the prevalence of coinfection is not well characterized in China. Prior studies have reported prevalence rates among individual populations that have varied significantly by mode of HIV transmission and by location.Methods: We performed a cross-sectional survey of three HIV-infected populations classified according to the route of HIV transmission, specifically, former plasma donors (FPDs), commercial sex workers and men who have sex with men, and intravenous drug users (IVDUs), and measured rates of HBV and HCV coinfection.Results: From June 2007 through December 2008, 624 FPDs, 512 IVDUs and 460 subjects infected with HIV through sexual transmission were enrolled into the study. We observed a prevalence of chronic HBV infection of 20% among IVDUs, 19% among those infected sexually and 3% among FPDs. The prevalence of an isolated positive test for hepatitis B core antibody was 27% among those infected sexually, 12% among IVDUs and 4% among FPDs. We observed the highest prevalence of HCV antibody seropositivity among IVDUs (94%), compared with 75% among FPDs and 27% among those infected sexually.Conclusion: Among three representing groups of HIV-infected patients in China, we observed a high prevalence of HBV and HCV coinfection with HIV. In order to reduce the morbidity and mortality associated with chronic coinfection, additional policies are needed for prevention and treatment.